Analisis Semiotika Roland Barthes Tentang Makna Pemilu Damai Dalam Film Kejarlah Janji - Silvia Dewi Anisa; M Rifa’i (Brand Communication, 2024)
This research aims to explore the meaning of a peaceful election as conveyed in the film "Kejarlah Janji" using Roland Barthes' semiotic approach. The research method used is descriptive qualitative. The primary data source for the research is the film "Kejarlah Janji," produced by KPU (General Elections Commission). The data collection technique employed is the documentary method. The data analysis technique used is content analysis. Based on the analysis of eleven scenes in the film, five main categories reflecting the meaning of a peaceful election were found, namely safe, orderly, peaceful, free from hoaxes, and free from money politics. Each category is analyzed through three stages: denotation, connotation, and myth according to Barthes' theory. The analysis results indicate that the meaning of a peaceful election includes security with reduced violence and intimidation, orderliness without code of ethics violations, minimal conflict and revenge, no spread of fake news, and high integrity and transparency without corruption and bribery in every stage of the election process.